Sensitivity Distribution Properties of a Phase-Shifted Fiber Bragg Grating Sensor to Ultrasonic Waves - Qi Wu; Yoji Okabe; Kazuya Saito; Fengming Yu (Sensors, 2014)
In this research, the sensitivity distribution properties of a phase-shifted fiber Bragg grating (PS-FBG) to ultrasonic waves were investigated employing the surface attachment method. A careful consideration was taken and examined by experimental results to explain that the distances and angles between the sensor and ultrasonic source influence not only the amplitudes, but also the initial phases, waveforms, and spectra of detected signals. Furthermore, factors, including the attachment method and the material’s geometric dimensions, were also discussed. Although these results were obtained based on PS-FBG, they are also applicable to a normal FBG sensor or even an optical fiber sensor, due to the identical physical changes induced by ultrasonic waves in all three. Thus, these results are useful for applications of optical fiber sensors in non-destructive testing and structural health monitoring.